Differential requirements in endocytic trafficking for penetration of dengue virus. - Eliana G Acosta; Viviana Castilla; Elsa B Damonte (PLoS ONE, 2012)
The entry of DENV into the host cell appears to be a very complex process which has been started to be studied in detail. In this report, the route of functional intracellular trafficking after endocytic uptake of dengue virus serotype 1 (DENV-1) strain HW, DENV-2 strain NGC and DENV-2 strain 16681 into Vero cells was studied by using a susceptibility to ammonium chloride assay, dominant negative mutants of several members of the family of cellular Rab GTPases that participate in regulation of transport through endosome vesicles and immunofluorescence colocalization. Together, the results presented demonstrate that in spite of the different internalization route among viral serotypes in Vero cells and regardless of the viral strain, DENV particles are first transported to early endosomes in a Rab5-dependent manner. Then a Rab7-dependent pathway guides DENV-2 16681 to late endosomes, whereas a yet unknown sorting event controls the transport of DENV-2 NGC, and most probably DENV-1 HW, to the perinuclear recycling compartments where fusion membrane would take place releasing nucleocapsid into the cytoplasm. Besides the demonstration of a different intracellular trafficking for two DENV-2 strains that shared the initial clathrin-independent internalization route, these studies proved for the first time the involvement of the slow recycling pathway for DENV-2 productive infection.